Dodecyl creatine ester improves cognitive function and identifies key protein drivers including KIF1A and PLCB1 in a mouse model of creatine transporter deficiency - Mabondzo, Aloïse; Harati, Rania; Broca-Brisson, Léa; Guyot, Anne-Cécile; Costa, Narciso; Cacciante, Francesco; Putignano, Elena; Baroncelli, Laura; Skelton, Matthew R.; Saab, Cathy; Martini, Emmanuelle; Benech, Henri; et al. (Frontiers in Molecular Neuroscience, 2023)
Creatine transporter deficiency (CTD), a leading cause of intellectual disability is a result of the mutation in the gene encoding the creatine transporter SLC6A8, which prevents creatine uptake into the brain, causing mental retardation, expressive speech and language delay, autistic-like behavior and epilepsy. Preclinical in vitro and in vivo data indicate that dodecyl creatine ester (DCE) which increases the creatine brain content, might be a therapeutic option for CTD patients. To gain a better understanding of the pathophysiology and DCE treatment efficacy in CTD, this study focuses on the identification of biomarkers related to cognitive improvement in a Slc6a8 knockout mouse model (Slc6a8-/y) engineered to mimic the clinical features of CTD patients which have low brain creatine content. Shotgun proteomics analysis of 4,035 proteins in four different brain regions; the cerebellum, cortex, hippocampus (associated with cognitive functions) and brain stem, and muscle as a control, was performed in 24 mice. Comparison of the protein abundance in the four brain regions between DCE-treated intranasally Slc6a8-/y mice and wild type and DCE-treated Slc6a8-/y and vehicle group identified 14 biomarkers, shedding light on the mechanism of action of DCE. Integrative bioinformatics and statistical modeling identified key proteins in CTD, including KIF1A and PLCB1. The abundance of these proteins in the four brain regions was significantly correlated with both the object recognition and the Y-maze tests. Functional analysis confirmed the key role of PLCB1, KIF1A and associated molecules in the pathogenesis of CTD